Chickpea in western Cuba: Agrodiversity fairs contributions - Cárdenas Travieso, Regla María (2021)
Introduction. The Cuban government has attached importance to the national production of chickpea, with the purpose of substituting imports, meeting market demands and contributing to food security and sovereignty. Objective. To present the contributions of the agro-diversity fairs in the selection of new chickpea (Cicer arietinum) genotypes in western Cuba. Materials and methods. The work was developed during the period 2000-2018. The selection of chickpea materials from six nurseries introduced by the National Institute of Agricultural Sciences (INCA) from the International Center for Agricultural Research in Dry Areas (ICARDA) and nine commercial varieties donated by the Institute for Fundamental Research in Tropical Agriculture (INIFAT) were analyzed. They were planted in three locations in the western region of Cuba. Agro-diversity fairs were held to select the genotypes with the best agricultural production performance. Results. The comparison between the international nurseries did not show significant agro- productive differences between them. The variables with the greatest weight in the agroproductive characterization were: days to maturation, days to flowering, number of branches, plant height, and yield. The largest number of genotypes selected in the agro-diversity fairs corresponded to the Elite International nursery for Latin American. The average yield of the selected materials was above 1.00 t ha-1. Conclusions. The holding of chickpea agro-diversity fairs has provided 17 new materials with suitable productive and culinary behavior and adaptability to the edaphoclimatic conditions of different locations in western Cuba.